Penyidikan Tindak Pidana Prostitusi secara Online - Yolla Fitri Amilia; Haryadi Haryadi; Dheny Wahyudi (Fakultas Hukum, Universitas Jambi, 2021)
This article aims to find out and analyze the process of investigating criminal acts of prostitution online in the jurisdiction of the Jambi City Police and find out what are the obstacles in the process of investigating criminal acts of prostitution online in the jurisdiction of the Jambi City Police Resort. The results of the study concluded that the online prostitution crime investigation process carried out by the Jambi City Resort Police officers in overcoming online prostitution crimes, the investigators carried out the investigation process by disguising themselves and trapping the perpetrators. In this case, the operational targets of the Jambi City Resort Police are commercial sex worker service providers (pimps). Furthermore, related to obstacles in the process of investigating criminal acts of prostitution online in the jurisdiction of the Jambi City Police, in fact, investigators in the investigation process have difficulty collecting evidence, and lack of human resources such as IT experts at the Jambi City Police Resort. Abstrak Â Artikel ini bertujuan untuk mengetahui dan menganalisis prosesÂ penyidikan prostitusi secara online di wilayah hukum Kepolisian Resor Kota Jambi dan mengetahui apakah hambatan dalam proses penyidikan tindak pidana prostitusi secara online di wilayah hukum Kepolisian Resor Kota Jambi. Hasil penelitian disimpulkan bahwa proses penyidikan tindak pidana prostitusi secara online yang dilakukan oleh aparat Kepolisian Resor Kota Jambi dalam menanggulangi prostitusi secara online, penyidik melakukan proses penyidikan dengan cara penyamaran dan penjebakan terhadap pelaku. Dalam hal ini yang menjadi target operasi penyidik Kepolisian Resor Kota Jambi ialah penyedia jasa pekerja seks komersil (mucikari). Selanjutnya, terkait hambatan dalam proses penyidikan tindak pidana prostitusi secara online di wilayah hukum Kepolisian Resor Kota Jambi pada kenyataannya, penyidik dalam proses penyidikan kesulitan dalam mengumpulkan alat bukti, dan kurangnya sumber daya manusia seperti ahli IT di Kepolisian Resor Kota Jambi.